Evaluasi Kebijakan Pemerintah Kota Tanjungpinang Dalam Pengembangan Objek Wisata Di Pulau Penyengat - Jesica Pasaribu; Fitri Kurnianingsih; Umrah Umrah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research refers to Regional Regulation No. 8 of 2018 of Tanjungpinang City, Chapter IV concerning Management of Tourism Objects article 7 (seven) paragraph 1 (one) which reads that those responsible for managing Penyengat Island cultural tourism are carried out by the Regional Government. The purpose of this research is to analyze the role of the Tanjungpinang City Culture and Tourism Office in developing tourism objects on Penyengat Island. The research method used is Descriptive Qualitative with a case study approach to determine the results in the study, with data collection techniques by observation, interview and documentation. The results showed that the Tanjungpinang City Culture and Tourism Office in implementing the Penyengat Island management policy was assisted by the Penyengat Island community in the form of a Tourism Awareness Group (POKDARWIS) which helped the Tanjungpinang City Culture and Tourism Office in implementing the Penyengat Island management policy. The conclusion of this research is that the policy evaluation process carried out by the Tanjungpinang City Culture and Tourism Office is to revitalize several parts and develop tourism on Penyengat Island with a religious and Malay cultural base. Thus, Penyengat Island is able to be visited by tourists with the intention and purpose of knowing the historical heritage of the phallus kingdom.